Academic Freedom, Tenure, and Student Evaluation of Faculty - Haskell, Robert E. (Education Policy Analysis Archives, 1997)
Despite a history of conflicting research on the reliability and validity of student evaluation of faculty (SEF) it has typically not been viewed as an infringement on academic freedom. When it is suggested that SEF may impinge on academic freedom, it is often considered an attack on either student rights, or on the process of evaluating faculty performance in general. Faculty and educational administrator views and surveys are reviewed as SEF is used in salary, promotion and tenure decisions. It is suggested that the literature shows that SEF infringe on instructional responsibilities of faculty by providing a control mechanism over curricular, course content, grading, and teaching methodology. It is further suggested that SEF play a significant role in current attacks on tenure, and that its role in a demographically diverse 21st century educational system has changed from its benign historical origins. It is concluded that contrary to current views, SEF is a serious unrecognized infringement on academic freedom.